An introduction to childhood and youth studies and psychology - Cooper, Victoria, 1967-; Tatlow-Golden, Mimi, 1963- (New York: Routledge, 2023)
"This exciting new book provides a novel interdisciplinary introduction to Childhood and Youth Studies and Psychology. Its accessible approach illuminates holistic understandings of children and young people's lives by drawing from multiple theoretical frameworks and wide-ranging research examples including case studies from around the world, featuring children and young people's perspectives throughout. Weaving insights from education and cultural studies, social anthropology, and sociology with social, cultural and developmental psychology, it covers children and young people's experiences and development from infancy to young adulthood (0-23 years) and their rights. Chapters explore key contemporary topics such as: - digital childhood and youth - children's embodied experiences - the social and cultural origins of selves - diverse families - race and ethnicity - global childhoods - models for understanding health and disability - children's rights and agency - gender and sexuality Essential reading for students on childhood and youth, psychology, and education courses, An Introduction to Childhood and Youth Studies and Psychology is also a valuable introductory resource for practitioners working with children and young people and for parents and policy makers with an interest in how we understand children and young people's lives today"--
What is childhood and youth studies -- The psychology of childhood and youth -- Children's bodies -- Making sense of the self -- Diverse families -- Young people's mental health -- Education, schools and learning in children and young people's lives -- Models of disability and their effects on children lives -- Race(ism) and ethnicity -- Global childhoods -- Gender in childhood -- Digital childhood and youth - Life with screens -- Adolescents, teenagers and youth: A time of change.
Includes bibliographical references and index.
Keywords: Child psychology; Youth -- Psychology